Peter Spier's circus! - Spier, Peter, 1927-2017. (New York : Doubleday, 1992)
A traveling circus arrives, sets up its village of tents, performs for the crowd, and then moves on again.
"A Doubleday book for young readers."
Keywords: Circus -- Fiction